(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A person’s likes anddislikes changes from time to time or, says it is very unstable. Anyone havinga need and is willing and able to sacrifice money is called consumer. Byignoring the preferences of the consumer the business community cannot possiblyfulfill its obligations in a responsible manner. The effect of variousexternal and internal factors on a consumer can be understood by differentpsychological theories. External factors include social habitat, correspondenceand friend circle etc. Internal factors comprise in a consumer psyche andothers like lifestyle, trends, personality, motivation etc. have a considerableon the response of the consumer. This research is something about that explainshow a buying process begins and the end result of buying decision. With thehelp of this study the relation of consumer behavior with the product, price,promotion etc is revealed. Thus, it is marketing mix which is indispensable forthe promotion of product/services in an organization. Research Paper – Thestudy on hair oils is also trying to find Consumer Preferences about differentfeatures of hair oils and how Packaging, Quantity, Easy Availability andVariety are affecting the sale of hair oil’s. Continuing scientific discoveriesand social changes, over the year been greatly responsible for the developmentsthat have taken place in the industry since, and brought hair oil, once aluxury, within the reach of everyone.